Characterization of a Fusobacterium necrophorum subspecies necrophorum outer membrane protein - Menon, Sailesh (Kansas State University, 2014)
Fusobacterium necrophorum is an anaerobic Gram-negative non spore forming rod shaped bacteria that is a normal inhabitant of the alimentary tract of humans and animals. Two subspecies of F. necrophorum have been recognized- subspecies necrophorum and subspecies funduliforme. Subspecies necrophorum is an opportunistic pathogen in animals causing diseases such as bovine hepatic abscesses and sheep foot rot while as subspecies funduliforme is linked with human oral and hepatic infections such as sore throats, Lemierre’s syndrome and hepatic abscesses. The pathogenic mechanisms of F. necrophorum are complex and are not well understood or defined. Several virulence factors such as leukotoxin, haemolysin, haemagglutinin and adhesin have been described. One of the most important factors in F. necrophorum bacterial pathogenesis is the adhesion of the bacteria to the host cell. The adhesion of the bacteria to the host cell helps it colonize the host tissue and this is followed by intracellular multiplication with dissemination to other tissues, which could ultimately lead to septicemia and death. Bacteria use adhesins which are proteins found in the outer membrane which help them bind with host receptors and this helps with the adhesion of the bacteria to the host cell. Not much is known about F. necrophorum adhesins. Here, we describe and characterize a novel adhesin.
Keywords: Fusobacterium necrophorum subspecies necrophorum; Outer membrane protein; Biology (0306)